The Sustainable Development Planning Based on Spatial Policy in Demak Regency - Sri Kusriyah; Aryani Witasari (Law Development Journal, 2023)
This research aims to find out how the implementation of the Regional Spatial Planning Policy in sustainable development planning, to find out how the process of permitting the use of spatial planning for development in Demak Regency. The method used in this paper is to use the normative juridical writing method, with the main data being secondary data in the form of documents related to the implementation of regional spatial planning policies in development planning and the process of permitting spatial use for development in Demak Regency, the data were analyzed by qualitative analysis with provide an interpretation of the data that has been collected. The results of the discussion show that 1) Sustainable development planning as outlined in the RPJMD is prepared based on the RPJPD. The preparation of the RPJMD also uses the RTRW as a reference for directing the location of activities and compiling development programs related to the use of space and areas, so that development is carried out in accordance with what has been planned in the RTRW. 2) The process of granting permits for development related to spatial and regional planning in the Demak Regency is carried out by the Public Works and Spatial Planning Office for the Demak Regency, abbreviated as Dinparu, has the task of assisting the Regent in carrying out government affairs in the field of public works and government affairs in the spatial planning sector which are the regional authority and co-administration assigned to the region. Dinputaru in the field of Spatial Planning encourages the public to use the online single submission (OSS) system in submitting suitability for spatial use activities (KPPR).